(untitled) (2009)
Information systems are sets of interacting elements aimed at supporting entrepreneurial or business activities; they cannot thus coexist in an isolated way but require their data to be shared so as to increase their productivity. Such systems' interoperability is normally accomplished through mark-up standards, query languages and web services. The literature contains work related to software system interoperability; however, it presents some difficulties, such as the need for using the same platforms and different programming languages, the use of read only languages and the deficiencies in the formalism used for achieving it. This paper presents a critical review of the advances made regarding heterogeneous software systems' interoperability. © 2010.